If it's not what You are looking for type in the equation solver your own equation and let us solve it.
60+3x-13=5x+7
We move all terms to the left:
60+3x-13-(5x+7)=0
We add all the numbers together, and all the variables
3x-(5x+7)+47=0
We get rid of parentheses
3x-5x-7+47=0
We add all the numbers together, and all the variables
-2x+40=0
We move all terms containing x to the left, all other terms to the right
-2x=-40
x=-40/-2
x=+20
| 1/6x+4=14 | | 19=h/2+16 | | 2k=4k-15 | | 3(x7)=181 | | 17x-14+5x-4=360 | | −7(1−6x)=−7(1+3x) | | 364/v=14 | | 2x+43+2x=5x+33 | | X(x+1)+(x+2)=75 | | 13=5-4v | | -9(-x+4)=18 | | 3=u/7-1 | | -15x=2/3 | | 12x+17=7x | | 35+82+x=180 | | 4/3=11/4a | | 20(v+3)-4v=4(4v+4)-18 | | k/2+9=13 | | -(10x^2)-4x+1=0 | | -1.5=6/n | | (5y+6)(4+y)=0 | | 10x+1/2=4x+1/4 | | -45=9t | | 2d+1+3(d-1)=-4-d-2 | | X²+2x=73 | | 18–2x=x+15 | | 10k^2+7k-6=0 | | 13x-2=x-2-4x | | 2x-0.15=0.55 | | 2/3x-5-2x=-13 | | 37+75+x=180 | | 7x-6=2(3x+4)-2 |